Salvaging the Infected Breast Tissue Expander: A Standardized Multidisciplinary Approach. Issue 6 (June 2016) - Viola, George M.; Selber, Jesse C.; Crosby, Melissa; Raad, Issam I.; Butler, Charles E.; Villa, Mark T.; Kronowitz, Steven J.; Clemens, Mark W.; Garvey, Patrick; Yang, Wei; Baumann, Donald P.
Abstract : Background: Infections of breast tissue expander (TE) are complex, often requiring TE removal and hospitalization, which can delay further adjuvant therapy and add to the overall costs of breast reconstruction. Therefore, to reduce the rate of TE removal, hospitalization, and costs, we created a standardized same-day multidisciplinary outpatient quality improvement protocol for diagnosing and treating patients with early signs of TE infection. Methods: We prospectively evaluated 26 consecutive patients who developed a surgical site infection between February 2013 and April 2014. On the same day, patients were seen in the Plastic Surgery and Infectious Diseases clinics, underwent breast ultrasonography with or without periprosthetic fluid aspiration, and were prescribed a standardized empiric oral or intravenous antimicrobial regimen active against biofilm-embedded microorganisms. All patients were managed as per our established treatment algorithm and were followed up for a minimum of 1 year. Results: TEs were salvaged in 19 of 26 patients (73%). Compared with TE-salvaged patients, TE-explanted patients had a shorter median time to infection (20 vs 40 days; P = 0.09), a significantly higher median temperature at initial presentation [99.8°F; interquartile range (IQR) = 2.1 vs 98.3°F; IQR = 0.4°F; P = 0.01], and a significantly longer median antimicrobial treatment duration (28 days; IQR = 27 vs 21 days; IQR = 14 days; P = 0.05). The TE salvage rates of patients whose specimen cultures yielded no microbial growth, Staphylococcus species, and Pseudomonas were 92%, 75%, and 0%, respectively. Patients who had developed a deep-seated pocket infection were significantly more likely than those with superficial cellulitis to undergo TE explantation ( P = 0.021). Conclusions: Our same-day multidisciplinary diagnostic and treatment algorithm not only yielded a TE salvage rate higher than those previously reported but also decreased the rate of hospitalization, decreased overall costs, and identified several clinical scenarios in which TE explantation was likely.